Pengaruh Daya Tarik Wisata, Persepsi Harga, Dan Kualitas Layanan Terhadap Niat Berkunjung Kembali Pada Objek Wisata Dunia Fantasi Ancol : Studi Kasus Pada Masyarakat Dki Jakarta - Dian Ashari; Andi Muhammad Sadat; Rahmi Rahmi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to examine the effect of tourist attractions, price perceptions, and service quality on revisit intentions. The data collection method uses a survey with an instrument in the form of a questionnaire distributed online. The population used is visitors to Dufan Ancol with the criteria of being residents of DKI Jakarta; aged 17 years and over; and have visited Dufan Ancol twice in the past year. This study involved 220 respondents, and the data was analyzed using SPSS Version 29 to manage data and analyze the results of the study using multiple linear regression equations. The results of the study indicate that 1) tourist attractions do not have a positive and significant effect on revisit intentions, 2) price perceptions have a positive and significant effect on revisit intentions, 3) service quality has a positive and significant effect on revisit intentions, 4) tourist attractions, price perceptions, and service quality simultaneously affect revisit intentions.